Antibacterial and Antibiofilm Activity of Green-Synthesized Zinc Oxide Nanoparticles Against Multidrug-Resistant Escherichia coli Isolated from Retail Fish - Mohamed Tharwat Elabbasy; Rasha M. El Bayomi; Esraa A. Abdelkarim; Abd El-Salam E. Hafez; Mohamed S. Othman; Mohamed E. Ghoniem; Mai A. Samak; Muteb H. Alshammari; Fahad Awwadh Almarshadi; Tamer Elsamahy; Mohamed A. Hussein (Molecules)
Multidrug-resistant (MDR) Escherichia coli is a major foodborne pathogen posing a critical threat to public health, particularly through the contamination of animal products. The increasing prevalence and virulence of MDR E. coli strains underscore the urgent need for alternative antimicrobial strategies. This study aimed to synthesize and characterize zinc oxide nanoparticles (ZnO-NPs) using Stevia rebaudiana as a sustainable capping and reducing agent, aligning with green chemistry principles. Of the 120 fish samples, 74.2% (89/120) were positive for E. coli contamination. Among the identified E. coli strains, 77.8% (119/153) were classified as MDR. Resistance profiling revealed 22 distinct patterns, and seven highly resistant and virulent strains were selected for further analyses. The eco-friendly auto-combustion synthesis of ZnO-NPs produced nanoparticles with semi-spherical to hexagonal shapes and an average size ranging from 12 to 25 nm. Scanning Electron Microscope–Energy Dispersive X-ray analysis (SEM-EDS) confirms that ZnO-NPs primarily consist of zinc (37.5%) and oxygen (19.9%), with carbon (42.6%) indicating the green synthesis process. ZnO-NPs demonstrated potent, dose-dependent antibacterial and antibiofilm activity against the selected MDR E. coli strains. Additionally, mechanistic studies revealed that ZnO-NPs disrupt bacterial cell membranes, alter cellular morphology, and interfere with DNA integrity. These findings highlight the potential of eco-friendly ZnO-NPs as a promising nanomaterial for enhancing food safety and addressing the growing challenge of MDR foodborne bacteria.